Orbital time scale records of Asian eolian dust from the Sea of Japan since the early Pliocene. (1st May 2018) - Zhang, Wenfang; De Vleeschouwer, David; Shen, Ji; Zhang, Zeke; Zeng, Lin
Abstract: A high-resolution potassium content record of sediments from Integrated Ocean Drilling Program (IODP) Site U1422 drilled in the northern Sea of Japan was employed to yield an astronomical timescale for this ∼205 m thick sedimentary archive. The K content was quantified using the natural gamma radiation (NGR) data routinely measured on DV JOIDES Resolution . The U1422 K (wt.%) series shows an increasing trend with time, which parallels the growth of North Hemisphere ice sheets since ∼4 Ma, as revealed by the global benthic foraminifer's oxygen isotope stack (LR04). We propose that K content variations reflect changes in the relative contributions of Asian eolian dust and volcanic weathering products, in response to changes in global ice volume. Using the shipboard age model, constrained by palaeomagnetism and nanofossils datums, we tuned the U1422 K content variations to the LR04 stack. Our tuned age model for site U1422 goes back to 3.9 Ma. The studied record indicates that Asian dust generation is enhanced during periods of global cooling. The synchronous variations between the U1422 K record and the LR04 stack also suggest that global cooling played a dominant role in promoting the central Asian aridification since ∼3.9 Ma, while the uplift of Tibetan Plateau plays a secondary role, considering many disagreements still exists between the timing and amplitude of the Qinghai-Tibetan uplift and the evolution of central Asian aridity since the early Pliocene. Highlights: Potassium (K) contents of IODP site U1422, Sea of Japan, reflects Asian dust contribution. K records vary in response to the global ice sheets. K variations were tuned to the global stacked benthic oxygen isotope curve. The tuning yields an accurate 3.9 Ma-age model for ∼205 m thick sedimentary archive.